Field reports of Iowa birds, December 6, 1986 - Bendorf, Carl J.et al (1986)
Bendorf lists birds sighted by various bird watchers across Iowa. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly Report of fall 1986. Epson - sheet feed